Ventricular injuries from direct trauma - Larre Borges, Uruguay; Filgueira, José L (Cirugía del Uruguay, 2020)
The paper gives an account_ of five cases oí ventricular wounds ( three of the right ventricle and two of the left) with a favourable evolution and total anatomical and functional restitution. The author points out th.at the therapeutical problem is one of surgical decision rather than one of surgical technique. Diagnosis · and therapy are considered and an ana1ysis is made of a new type of lesion produced as a consequence of surgical diagnosis manoeuvres.